The Jewish Catacomb at Vigna Randanini in Rome.: A New Architectural and Archaeological Study. With an Appendix on Tomb Statistics - Zimmermann, Norbert; Rutgers, Leonard V.; Kodzoman, Eva; Vilella, Antonello; Dee, Michael W. (Römische Mitteilungen, 2022)
In this article, we present a fresh and comprehensive study of the Jewish catacomb at Vigna Randanini based on a thorough investigation of the architecture of this underground cemetery and of the archaeological materials it still contains. Having conducted a complete 3D-documentation of the monument with a Laserscanner, we first present a new and reliable plan for the site. We then use this as point of departure for a detailed architectural study in the course of which we identify four major consecutive building phases. Moving on to the wall paintings, we offer a full description and documentation, which we then contextualize by discussing the issue of possible Jewish ownership. Reviewing the funerary inscriptions from Vigna Randanini, we highlight the importance of studying these in their original topographical context, offering new insights into chronology and the importance of family burial. This is followed by a presentation of radiocarbon data that indicate that burial started somewhat earlier and continued longer than previously thought. In a final concluding section, we put all the data together and discuss how our findings impinge on our understanding of the topography, the chronology and the question of the religious affiliation of the monument. In an appendix we present a preliminary study of the tombs in Vigna Randanini, which we investigate from the perspective of historical demography.